Evaluation of commercially available class A water-based foam concentrates for swine depopulation - Dawn M. Torrisi; Magnus R. Campler; Janice Y. Park; Ting-Yu Cheng; Brad L. Youngblood; Talita P. Resende; Michael D. Cressman; Justin D. Kieffer; Andréia G. Arruda; Andrew S. Bowman (PLoS ONE, 2025)
Currently, the swine industry is lacking an efficient method for large-scale emergency depopulation. Class A water-based foam (WBF) has been demonstrated as a viable option for large-scale depopulation of pigs in all stages of development. However, these studies exclusively used the PHOS-CHEK WD881 (WD881) Class A foam concentrate based on previously demonstrated efficacy for depopulation. This study investigated the suitability of 15 other commercially available WBF concentrates for depopulation based on foaming performance, physiological effects, and efficacy. The performance of each product was evaluated and compared to WD881 at 0.5, 1.0 and 3.0% water-foam concentrations for low- and high-pressure pump systems. The time to fill an 11.5 m3 construction container and decay rate over a 10-minute dwell time were assessed for each WBF. Top-performing foams were further evaluated for behavior and short-term physiological changes and gross lesions during a 15-minute exposure test on piglets. Finally, the top-performing foams were tested for their suitability to depopulate adult swine during large-scale field conditions. Subcutaneous dataloggers recorded swine activity which was used to estimate the time to cessation of movement (COM), an approximate analog for loss of consciousness. Four WBF concentrates (FireIce Polar EcoFoam, Buckeye Platinum, National Foams Knockdown and BioFor N) were shortlisted based on performance at 1% concentration. These products had a mean (±SD) fill time of 62.4s (± 14.9) and decay rate of 0.5 (± 0.66) cm/min compared to WD881 with 50.0s (± 3.5) and 0.2 (± 0.1) cm/min, respectively. No differences between treatment groups were observed during the exposure testing and subsequent necropsy. For the large-scale field trials, the mean (±SE) time to COM was 151.5 s (±10.5). All foams achieved 100% mortality of swine. This study identified four additional WBFs suitable for swine depopulation which are commercially available on the U.S market. These additional WBF options may facilitate large-scale swine depopulation during widespread infectious disease outbreaks by mitigating potential bottlenecks resulting from product availability.